Mengenal Dunia Digital Sejak Dini: Pelatihan Microsoft Word untuk Anak Sekolah Dasar - Muhammad Furqon; Lilis Suharti; Siti Komala; Leonita Maharani; Achdan Firjatullah; Durotun Nisah; Muhammad Sulton (Pusat Riset dan Inovasi Nasional, 2025)
In today’s digital era, early mastery of basic technology is essential. This community service program aimed to introduce Microsoft Word, a fundamental word-processing tool, to elementary school students in Cempaka Village. The training targeted 5th and 6th graders, most of whom had limited or no experience with computer applications. Using a hands-on,